Psychometric properties of the Urdu version of the Geriatric Oral Health Assessment Index (GOHAI) and oral health‐related quality of life in the elder Pakistani population. (5th January 2021) - Chaudhary, Farooq Ahmad; Siddiqui, Yasir Dilshad; Yaqoob, Muhammad Azeem; Khalid, Muhammad Danial; Butt, Danial Qasim; Hameed, Shoaib
Abstract: Objective: The study aimed to translate the English version of the Geriatric Oral Health Assessment Index, assess its reliability and validity, and demonstrate its psychometric properties with regard to OHRQoL in the elder Pakistani population. Material and methods: In this cross‐sectional study, 408 elder people were randomly recruited from three day‐care centres. In the translation process, the translated Urdu version was reviewed by a committee of experts, followed by back‐translation into English and re‐reviewed by the same committee of experts. The questionnaire sought information about socio‐demographic characteristics information and self‐perception of oral, general health and treatment needs. OHRQoL was examined using GOHAI‐U, and intraoral examination recorded the decayed, missing, and filled teeth. Reliability, internal consistency, convergent and discriminant validity of GOHAI‐U were examined. Results: The mean GOHAI‐U score was 40.2 (SD = 5.7, range = 20‐55). The Cronbach's alpha for GOHAI score was 0.71, item‐scale correlation coefficients ranged from 0.63 to 0.76, and test–retest correlation ranged from 0.59 to 0.74. Three factors supported the theoretical construction in the component factor analysis of the index. For convergent validity, there was a significant relationship between the GOHAI score and self‐perceived oral, general health and treatment needs ( P  < .05). For discriminant validity, a significant correlation was found between the GOHAI score and clinical measures of dental health status except with the carious teeth. Conclusion: The GOHAI‐U has sufficient reliability and constructs validity to be used as an efficient measure of oral health‐related quality of life in the Pakistani elder population.